HUMAN RIGHTS PROTECTION IN EMERGENCY CIRCUMSTANCES: SCOPE AND LIMITATIONS OF ARTICLE 15 OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS - Kreštalica, Sanja; Petković, Simeon (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
This paper examines the legal framework for the protection of human rights in situations of extreme crisis in the European legal area, in order to achieve a coherent understanding of legal standards that will lead to their more uniform application. Through an in-depth analysis of the meaning and scope of the provisions of Article 15 of the European Convention, as well as the corresponding practice of the European Court of Human Rights, the authors determine under what conditions the suspension of certain rights and freedoms is legally permissible, and which state measures adopted in extraordinary circumstances represent the protection of the public interest, and which go beyond the scope of the most necessary measure required by the given situation and represent a violation of the rights and freedoms of the individual.This work is based on the idea that specific limitations for the enjoyment of human rights are necessary and justified. It is a well-known that only a limited number of human rights are absolute and as such are immune to any restrictions regardless of the circumstances and justifications. However, this does not reduce the need for the measures that the state resorts to in times of crisis to be strictly controlled.
Keywords: human rights, European convention on human rights, derogations, emergency powers